Development of a range of fluorescent reagentless biosensors for ATP, based on malonyl-coenzyme A synthetase. - Renée Vancraenenbroeck; Simone Kunzelmann; Martin R Webb (PLoS ONE)
The range of ATP concentrations that can be measured with a fluorescent reagentless biosensor for ATP has been increased by modulating its affinity for this analyte. The ATP biosensor is an adduct of two tetramethylrhodamines with MatB from Rhodopseudomonas palustris. Mutations were introduced into the binding site to modify ATP binding affinity, while aiming to maintain the concomitant fluorescence signal. Using this signal, the effect of mutations in different parts of the binding site was measured. This mutational analysis revealed three variants in particular, each with a single mutation in the phosphate-binding loop, which had potentially beneficial changes in ATP binding properties but preserving a fluorescence change of ~3-fold on ATP binding. Two variants (T167A and T303A) weakened the binding, changing the dissociation constant from the parent's 6 μM to 123 μM and 42 μM, respectively. Kinetic measurements showed that the effect of these mutations on affinity was by an increase in dissociation rate constants. These variants widen the range of ATP concentration that can be measured readily by this biosensor to >100 μM. In contrast, a third variant, S170A, decreased the dissociation constant of ATP to 3.8 μM and has a fluorescence change of 4.2 on binding ATP. This variant has increased selectivity for ATP over ADP of >200-fold. This had advantages over the parent by increasing sensitivity as well as increasing selectivity during ATP measurements in which ADP is present.